Pengaruh Sistem Informasi Akuntansi (SIA) terhadap Pengendalian Internal di Perusahaan - Jecky Indramarta; Rizky Syafputra (Journal on Education, 2024)
This research aims to understand the influence of Accounting Information Systems (AIS) on internal control in companies that utilize AIS. This research uses qualitative research methods so that the results are presented using descriptive analysis. The discussion in this research explains that the policies and procedures that exist in each company are intended to provide guarantees that the goals that have been set and the rules that have been set can be achieved and adhered to, and are a form of management control that is also used to provide reliable and guaranteed financial information. compliance with applicable laws and regulations.